Answer:
- h(c) = -0.19(c - 1)²(c + 1)
Explanation:
We need to find an equation of h(c) with the following info given:
- h is of degree 3
- c = 1 is the zero with multiplicity of 2
- h(-1) = 0
- h(0) = - 0.19
According the info above we have factors:
- h(c) = (c - 1)²(kc + t), where k and t unknown for now
Let's work out the value of k and t:
- h(-1) = (- 1 - 1)²(-k + t) = 0 ⇒ - k + t = 0 ⇒ k = t
- h(0) = (0 - 1)²(k*0 + t) = - 0.19 ⇒ t = - 0.19 ⇒ k = -0.19
We now have the factors:
- h(c) = (c - 1)²( - 0.19c - 0.19) ⇒
- h(c) = -0.19(c - 1)² (c + 1)